Creation of e-pathfinders for the graduate and undergraduate subjects of the University of the Philippines School of Library and Information Studies - Santos, Jonathan F.
Much effort is needed to sustain the development of a culture of research in the field of library and information science (LIS). The creation of additional finding tools such as pathfinders or research guides will greatly help library users in their academic and research works. Electronic pathfinders provide a unique opportunity for librarians since they function as guides to resources available in a particular library while capitalizing on the various capabilities of the Internet in terms of access. With various options on the implementation of e-pathfinders currently available, providing this service is something librarians should highly consider.